An allosteric modulator activates BK channels by perturbing coupling between Ca2+ binding and pore opening - Guohui Zhang; Xianjin Xu; Zhiguang Jia; Yanyan Geng; Hongwu Liang; Jingyi Shi; Martina Marras; Carlota Abella; Karl L. Magleby; Jonathan R. Silva; Jianhan Chen; Xiaoqin Zou; et al. (Nature Communications, 2022)
Ca2+ activated BK channels are important for neural and muscle function. Here authors use a compound, BC5, to show that the interface between the cytosolic and voltage sensing domains is a major allosteric pathway for Ca2+ binding to open the channel.